2020
DOI: 10.1111/bjd.19155
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective cohort study of pregnancy outcomes in hidradenitis suppurativa

Abstract: side-effects and/or fear of relapse remained stable during patients' follow-up. Unexpectedly, the TABQOL scores measured at the time of inclusion of the population of prevalent patients, and at month 6 in incident cases, were not significantly different between patients taking topical corticosteroids, oral prednisone and/or immunomodulators, or immunosuppressants (P = 0Á96 and P = 0Á56, respectively). Overall, this large multicentre study provides evidence that the ABQOL score is a robust tool, sensitive to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
1
10
0
1
Order By: Relevance
“…12,13,16,29 What is more, lesions on the breasts can hinder lactation, which is why they should be treated timely. 11,12 There is also evidence that women with HS fear their child will have the disease, or delivery will be more di cult because of it. 22 Our study showed that most women worry about potential di culties during pregnancy and the postpartum, including whether they will be t enough to properly take care of their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,16,29 What is more, lesions on the breasts can hinder lactation, which is why they should be treated timely. 11,12 There is also evidence that women with HS fear their child will have the disease, or delivery will be more di cult because of it. 22 Our study showed that most women worry about potential di culties during pregnancy and the postpartum, including whether they will be t enough to properly take care of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the detrimental disease symptoms and sequalae common to both men and women, the latter also face di culties germane to their gender, such as menstruation-related ares, adverse pregnancy outcomes, limitations regarding treatment during pregnancy and the postpartum, birth and breastfeeding challenges, issues with pelvic examination, as well as breast examination and imaging tests. 2,10,[12][13][14][15][16] What is more, women seem to fare worse on quality-of-life endpoints comparing to their male counterparts: their overall sexual impairment is greater, they are more likely to have body image issues, have greater fear of rejection when it comes to relationships and manifest signi cantly more symptoms of depression. 5,[17][18][19][20] The impact of HS is felt by patients' families as well.…”
Section: Introductionmentioning
confidence: 99%
“…Higher BMI in women with fulfilled reproductive desires may be explained by their older age, as BMI is positively correlated with age [46], and the increasing weight gain between consecutive pregnancies, even in women without pre-existing obesity [47]. Weight gain is known to contribute to HS pathogenesis [48], while the effect of pregnancy on HS [49] as well as the effect of HS on pregnancy are unknown [50,51]. Although a high rate of HS exacerbation during pregnancy and postpartum has been reported, most patients did not receive HS-directed medical treatment or care from a dermatologist during their pregnancy [51].…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found that rates of live births, likelihood of caesarean section and increased risk of gestational hypertension, preeclampsia, pregnancy complication or neonatal complication were not significantly associated with baseline HS severity. Interestingly, they observed (i) that in more than 10% of pregnancies women continued to use tobacco or marijuana during pregnancy, (ii) that the proportion of non-breastfeeding women was significantly higher in patients with HS breast lesions compared to those without HS breast lesions ( Figure 2 ) and (iii) significantly higher average rates of gestational hypertension and pre-eclampsia compared to the US general population [ 152 ].…”
Section: Hs and Pregnancymentioning
confidence: 99%
“…Abbreviation: HS, hidradenitis suppurativa. Information extracted from references [ 72 , 86 , 87 , 112 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 152 , 157 , 158 , 168 , 169 , 173 , 174 ].…”
Section: Hs Tattooing and Body Artmentioning
confidence: 99%